2017
DOI: 10.2147/nss.s103462
|View full text |Cite
|
Sign up to set email alerts
|

Update on the treatment of narcolepsy: clinical efficacy of pitolisant

Abstract: Narcolepsy is a neurological disease that affects 1 in 2,000 individuals and is characterized by excessive daytime sleepiness (EDS). In 60–70% of individuals with narcolepsy, it is also characterized by cataplexy or a sudden loss of muscle tone that is triggered by positive or negative emotions. Narcolepsy decreases the quality of life of the afflicted individuals. Currently used drugs treat EDS alone (modafinil/armodafinil, methylphenidate, and amphetamine), cataplexy alone (“off-label” use of antidepressants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Narcolepsy with cataplexy is a chronic neurological sleep‐wake disorder. The narcolepsy prevalence has been estimated in the range 0.02‐0.05 5% . The age of onset varies between individuals and has a bimodal pattern, peaking at the age of 15 and 36 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Narcolepsy with cataplexy is a chronic neurological sleep‐wake disorder. The narcolepsy prevalence has been estimated in the range 0.02‐0.05 5% . The age of onset varies between individuals and has a bimodal pattern, peaking at the age of 15 and 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The narcolepsy prevalence has been estimated in the range 0.02-0.05 5%. [1][2][3][4] The age of onset varies between individuals and has a bimodal pattern, peaking at the age of 15 and 36. 5 A recent review demonstrated that the relative risk for developing narcolepsy after Pandemrix vaccination increased fivefold to 14-fold in children and adolescents and twofold to sevenfold in adults, during the first year after vaccination.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Pitolisant is a new drug with a specific action that increases hypothalamic levels of histamine by antagonising histamine (H3) auto-receptors in the tuberomammillary nucleus, the origin of wake-promoting histaminergic neurones 30. Recent placebo-controlled studies have confirmed a modest positive effect on cataplexy symptoms with improved wakefulness in people with narcolepsy 31.…”
Section: Treatmentmentioning
confidence: 99%